1985
DOI: 10.1002/mrc.1260230804
|View full text |Cite
|
Sign up to set email alerts
|

Steric interaction between the peripheral substituents of 10(S)‐chlorophyll derivatives and its conformational consequences: A proton magnetic resonance study

Abstract: The improved methods developed recently for the preparation of lo(@-chlorophyll derivatives have permitted a detailed comparison of their conformations with those of the corresponding 10(R) derivatives, utilizing ' H NMR spectroscopy. Starting from the highly purified lo(@ derivative and following its conversion to the corresponding 10(R) form by repeated ' H NMR spectral measurements in acetone-&, reliable values for the differences in the chemical shifts (As) for each epimeric pair of compounds have been obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Note. Compiled information from this work and published sources (23,30,31 ). The numbering is according to Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note. Compiled information from this work and published sources (23,30,31 ). The numbering is according to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A low concentration ensured that the Chl a exists in the monomeric form, in line with previous work (30,31). By using newly obtained and published data, a complete set of 1 H and 13 C shifts σ H liq , σ C liq for a monomer in solution was produced ( Table 2).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Peak 2a is probably chlorophyll a esterified with cis-phytol (see Fig. 5 (Hynninen and Lotjonen 1985) considering the low-field shift of the 13'-H signal introduced by pyridine (Abraham et al, 1989). To see whether chlorophyllide a'can be esterified at all, we incubated a mixture of chlorophyllide &a' (containing 3 0 2 3 % a?…”
Section: Investigation Of Chlorophyllidesmentioning
confidence: 99%
“…Chl a′ is thermodynamically less stable than Chl a due to the steric hindrance between these bulky substituents (the equilibrium Chl a′ mole fraction ) 0.24, see ref 17). Though visible absorption 18,19 and fluorescence spectra (Oba et al, unpublished results) and redox properties (Mazaki et al and Iijima et al, unpublished results) of Chl a and a′ are almost the same due to a common π-conjugated system, the epimers are distinguished from each other by NMR 20,21 and CD spectra, 18,19 rate of pheophytinization (demetalation), [22][23][24] reducibility of the C13 1 -keto carbonyl moiety, 24 and elution behaviors in high-performance liquid chromatography (HPLC). 25 Hynninen and co-workers reported that Chl a′ was more soluble 23 and had a somewhat weaker intermolecular aggregation tendency in nonpolar organic solvents than Chl a.…”
Section: Introductionmentioning
confidence: 99%